Morphological and molecular characterization of selected amphibians from Andhra Pradesh (Zoological Records and Reviews, 2021)
Andhra Pradesh, situated at the interface of the Eastern Ghats and the Deccan Plateau, harbours a poorly inventoriedamphibian fauna despite its high topographic and ecological heterogeneity. This study presents integrated morphologicaland molecular characterization of 14 amphibian species sampled from six districts of Andhra Pradesh during themonsoon seasons of 2018 and 2019. Morphometric measurements (18 variables per individual) and qualitativecharacters (skin texture, toe-webbing, tympanum visibility, and colouration) were recorded for 284 individuals acrossAnura (12 species) and Gymnophiona (2 species). Mitochondrial 16S rRNA gene sequences (550 bp) were generated for84 individuals. Bayesian phylogenetic analysis resolved seven well-supported clades congruent with current family-leveltaxonomy. Morphometric discriminant function analysis correctly assigned 91.4% of individuals to their species based oneight morphometric ratios. Two populations of Nyctibatrachus cf. humayuni from the Nallamala Hills exhibited 16Spairwise distances of 6.8-7.4% from reference sequences, suggesting the presence of at least one undescribed species.Species distribution models fitted to climatic predictors identified 34.2% of suitable habitat as falling outside existingprotected area boundaries, highlighting substantial gaps in the current protected-area network for amphibianconservation in Andhra Pradesh.